Controlling Factors of Methane in Tropical Lakes of Different Depths. Issue 4 (6th April 2021) - Mendoza‐Pascual, Milette U.; Itoh, Masayuki; Aguilar, Jaydan I.; Padilla, Karol Sophia Agape R.; Papa, Rey Donne S.; Okuda, Noboru
Abstract: To understand methane (CH4 ) dynamics in tropical lakes and describe their importance in overall CH4 emissions, we observed temporal trends of CH4 stored in the water columns of Philippine lakes of different depths (shallow, moderately deep, and deep). We detected higher CH4 stored in profundal anoxic layers of deeper lakes. The average surface and profundal CH4 concentrations throughout our monthly monitoring were 0.27 ± 0.07 and 421 ± 189 μmol L –1 in the shallow lake, 0.48 ± 0.37 and 1, 121 ± 125 μmol L –1 in the moderately deep lake, and 0.34 ± 0.23 and 943 ± 119 μmol L –1 in the deep lake. The fate of CH4 stored in the water column was related to depth, owing to different stratification and mixing regimes. Analyses of temporal relationships of CH4 with daily weather and physicochemical parameters revealed their impact on CH4 dynamics by controlling the frequency and mixing intensity throughout the year. Only shallow lake exhibited increase in CH4 concentrations with lowering atmospheric pressure. This allows vertical mixing and transport of CH4 from deeper to shallower layers. In moderately deep, and deep lakes, effects of daily weather parameters were not apparent on CH4 concentrations in the deepest layers (below 30 m depth). This suggests that lake depth and stratification should be considered for precise estimation of tropical lakes' CH4 emissions. Comparison with lakes under different climate conditions revealed the importance of tropical lakes for surface CH4 emission due to higher surface CH4 concentrations. Changes in water temperature is one of the factors controlling profundal CH4 production, storage, and its transport to shallower layer. Key Points: Vertical CH4 storage distribution in studied lakes are linked to episodic events, such as monsoons and extreme weather, driving turnover Weather variables such as air temperature and atmospheric pressure are external drivers of stored methane in tropical lakes Tropical lakes, with higher profundal water temperature, show more potential for storing and emitting CH4 than lakes from other regions